2022
DOI: 10.3389/fphar.2022.976156
|View full text |Cite
|
Sign up to set email alerts
|

Vanillic acid attenuates H2O2-induced injury in H9c2 cells by regulating mitophagy via the PINK1/Parkin/Mfn2 signaling pathway

Abstract: Vanillic acid, a phenolic compound mainly obtained from the foot of Picrorhiza scrophulariiflora Pennell, has been demonstrated to possess a cardiovascular-protective effect in previous studies. However, there is lack of research on vanillic acid protecting cardiomyocytes from oxidative stress injury by mediating mitophagy. In the present study, oxidative stress injury in the H9c2 cell line was induced by H2O2. Our results confirmed that vanillic acid mitigated apoptosis and injury triggered by oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In the current we observed the beneficial effects of vanillic acid on ENU-induced mitochondrial dysfunctions in mouse isolated lymphocytes. Our findings, consistent with previous studies [46] , [47] , [48] suggest that vanillic acid via its mitoprotective effects can protect mitochondrial dysfunction induced by different chemicals, which may finally lead to toxicity and cancer development induced.…”
Section: Discussionsupporting
confidence: 93%
“…In the current we observed the beneficial effects of vanillic acid on ENU-induced mitochondrial dysfunctions in mouse isolated lymphocytes. Our findings, consistent with previous studies [46] , [47] , [48] suggest that vanillic acid via its mitoprotective effects can protect mitochondrial dysfunction induced by different chemicals, which may finally lead to toxicity and cancer development induced.…”
Section: Discussionsupporting
confidence: 93%
“…More than 20 kinds of C3G metabolites (C3G-Ms) in serum have been identified [ 64 ]. Among them, protocatechuic acid [ 65 , 66 , 67 ], vanillic acid [ 68 , 69 ] or their derivatives are the main bioactive metabolites, which have antioxidant and anti-inflammatory activities. The metabolites of C3G detected in this study were protocatechoic acid, methyl 3,4-dihydroxybenzoate, vanillic acid, 4-hydroxybenzeneacetic acid, et al, which may increase C3G bioavailability and contribute to the repair of gut mucosal barrier and intestinal microbiota disorder [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning this last aspect, it has been observed that treatment with VA results in an upregulation of eNOS expression and a downregulation of endothelin-1 [ 116 ]. Furthermore, VA has been shown to exert its cardioprotective effects by modulating AMPK signaling pathways and upregulating endogenous antioxidant markers such as superoxide dismutase, catalase, glutathione peroxidase, and total antioxidant capacity [ 115 , 117 , 118 ], while an in vitro study conducted on H9c2 cell line showed that VA protection versus H 2 O 2 damage could be mediated via the regulation of PINK1/Parkin/Mfn2 signaling pathway [ 119 ]. Moreover, VA treatment showed anti-inflammatory properties by reducing proinflammatory cytokines, particularly IL-1β, IL-6, and TNF-α [ 117 ], and modifying microbiota composition, restoring the relative abundance of Lactobacillus and decreasing Bacteroides genera [ 120 ].…”
Section: Anthocyanins and Their Gut-microbiota Derived Metabolites On...mentioning
confidence: 99%